Penerapan Kurikulum Merdeka Belajar Pada Mata Pelajaran Sejarah Di SMA Negeri 04 Kota Jambi - Hawarulaini, Latifa; Mareta, Yoan; Purnomo, Budi (Pendidikan Sejarah FKIP Universitas JAMBI, 2024)
This article is prepared based on how the Implementation of Merdeka Belajar Curriculum at SMA N 04 in History Subjects in Jambi City. Qualitative research is a systematic and analytical research or research that builds a cultural reconstruction of a group of people where culture is a reflection of the views of the group as a whole society. This research is used using descriptive qualitative research methods. The data collection technique used in this paper uses primary data, namely by collecting data directly by examining the object concerned. This paper aims to describe and examine more deeply the Merdeka Curriculum in history subjects. The results showed that SMA N 04 Jambi City has efficiently implemented the Independent Curriculum in history subjects, training students' thinking skills by using presentation or discussion methods.